Underdog or Top Dog Brand Story? The Role of Self-Construal and Need of Uniqueness - Li, Yalin; Zhao, Min (Frontiers in Psychology, 2021)
The design of an effective brand story has become a key issue in marketing strategies. This study aims to explore what kinds of brand stories (underdog or top dog) individuals prefer from the perspective of the level of self-construal and the need for uniqueness. In this study, a questionnaire survey was used to collect data from China. One-way analysis of variance and bootstrapping via the Process plug-in were adopted to test the hypotheses. This study confirms that individuals with independent self-construal have a higher need for uniqueness and prefer underdog brand stories, while individuals with interdependent self-construal have a lower need for uniqueness and prefer the top dog brand story. This paper promotes theoretical research in the fields of self-construal, the need for uniqueness, and brand stories, and provides rich theoretical support for enterprises in designing and adjusting brand stories. Implications, limitations and future studies are discussed.